Rho-Kinase Inhibition Ameliorates Metabolic Disorders through Activation of AMPK Pathway in Mice - Noda, Kazuki; Nakajima, Sota; Godo, Shigeo; Saito, Hiroki; Ikeda, Shohei; Shimizu, Toru; Enkhjargal, Budbazar; Fukumoto, Yoshihiro; Tsukita, Sohei; Yamada, Tetsuya; Katagiri, Hideki; Shimokawa, Hiroaki (PLOS ONE, 2014)
Background Metabolic disorders, caused by excessive calorie intake and low physical activity, are important cardiovascular risk factors. Rho-kinase, an effector protein of the small GTP-binding protein RhoA, is an important cardiovascular therapeutic target and its activity is increased in patients with metabolic syndrome. We aimed to examine whether Rho-kinase inhibition improves high-fat diet (HFD)-induced metabolic disorders, and if so, to elucidate the involvement of AMP-activated kinase (AMPK), a key molecule of metabolic conditions. Methods and Results Mice were fed a high-fat diet, which induced metabolic phenotypes, such as obesity, hypercholesterolemia and glucose intolerance. These phenotypes are suppressed by treatment with selective Rho-kinase inhibitor, associated with increased whole body O2 consumption and AMPK activation in the skeletal muscle and liver. Moreover, Rho-kinase inhibition increased mRNA expression of the molecules linked to fatty acid oxidation, mitochondrial energy production and glucose metabolism, all of which are known as targets of AMPK in those tissues. In systemic overexpression of dominant-negative Rho-kinase mice, body weight, serum lipid levels and glucose metabolism were improved compared with littermate control mice. Furthermore, in AMPKα2-deficient mice, the beneficial effects of fasudil, a Rho-kinase inhibitor, on body weight, hypercholesterolemia, mRNA expression of the AMPK targets and increase of whole body O2 consumption were absent, whereas glucose metabolism was restored by fasudil to the level in wild-type mice. In cultured mouse myocytes, pharmacological and genetic inhibition of Rho-kinase increased AMPK activity through liver kinase b1 (LKB1), with up-regulation of its targets, which effects were abolished by an AMPK inhibitor, compound C. Conclusions These results indicate that Rho-kinase inhibition ameliorates metabolic disorders through activation of the LKB1/AMPK pathway, suggesting that Rho-kinase is also a novel therapeutic target of metabolic disorders.